Overview of residual stress in MEMS structures: Its origin, measurement, and control - Dutta, Shankar; Pandey, Akhilesh (Journal of materials science. Materials in electronics, 2021)
Micro-electro-mechanical system (MEMS) technology has radically changed the scale, performance, and cost of a wide variety of sensors and actuators by taking advantage of batch fabrication. The multidisciplinary nature of MEMS employs knowledge of diverse technical areas to realize improved and novel transducer systems. This also brings various associated challenges that are otherwise being ignored in a simple macro-dimensional system. MEMS devices typically comprise several deposited thick and thin films as well as bonded of dissimilar materials (like silicon, metal, glass, etc.). Residual stress is one of the most common outcomes during this integration/stacking of distinctly different materials for the fabrication of novel MEMS structures. The residual stress may significantly affect the performance and reliability of the fabricated devices. Thus, the evaluation and regulation of residual stress are one of the crucial aspects to assess the functioning of modern-day MEMS devices. This paper reviewed the origins of residual stress in MEMS fabrication processes. Different techniques involved in testing and characterization of the residual stresses are reviewed. Few important case studies are discussed to highlight the effect of residual stress (generated during various fabrication processes) on characteristics of different MEMS structures. The brief overview of the possible route to minimize the residual stresses is also presented.